Development of an Augmented Reality (AR)-Based Indoor Navigation Application for Evacuation and Emergency Handling in UIN Sunan Ampel Surabaya Building - Utama, Arya Prayogi; Ridwan, Mujib; Izzuddin, Muhammad Andik (Institut Teknologi Bisnis AAS Indonesia, 2024)
The management of emergency situations in buildings is a crucial aspect of occupational health and safety (OHS). Fast and efficient evacuation is essential to ensure the safety and well-being of all individuals within the building. To address this need, this research developed a marker-based augmented reality (AR) application to support evacuation and emergency handling. The application was built using the Unity game engine, the A* algorithm for navigation, and Unity Navmesh for environment modeling. The development process followed systematic research methods, including needs analysis, design, development, testing, and system evaluation. Implemented in C# programming language, the application integrates ARCore for AR features and ZXing for QR code decoding. Testing results demonstrated that the application provides accurate and efficient evacuation guidance, with a navigation accuracy averaging a margin of error of 1.12 meters. Additionally, the Image Tracking feature enables recognition of emergency equipment, further supporting emergency response. The application functions reliably under various lighting conditions, ranging from 878 lux to 1 lux. By integrating these capabilities, this system is anticipated to enhance the efficiency and effectiveness of evacuation and emergency handling processes in multi-story buildings.